If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Xsquared + 4x + -12 = 0 Reorder the terms: -12 + adeqrsuX + 4x = 0 Solving -12 + adeqrsuX + 4x = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '12' to each side of the equation. -12 + adeqrsuX + 12 + 4x = 0 + 12 Reorder the terms: -12 + 12 + adeqrsuX + 4x = 0 + 12 Combine like terms: -12 + 12 = 0 0 + adeqrsuX + 4x = 0 + 12 adeqrsuX + 4x = 0 + 12 Combine like terms: 0 + 12 = 12 adeqrsuX + 4x = 12 Add '-4x' to each side of the equation. adeqrsuX + 4x + -4x = 12 + -4x Combine like terms: 4x + -4x = 0 adeqrsuX + 0 = 12 + -4x adeqrsuX = 12 + -4x Divide each side by 'deqrsuX'. a = 12d-1e-1q-1r-1s-1u-1X-1 + -4d-1e-1q-1r-1s-1u-1xX-1 Simplifying a = 12d-1e-1q-1r-1s-1u-1X-1 + -4d-1e-1q-1r-1s-1u-1xX-1
| 10-(15-2x)=3(2x-7-2)(9x-x) | | 2n+3n-10=20 | | 7a+1=5 | | 2(x_3)+x=3_2(x_8) | | 60+3x=3x | | 2x+7.99c=24 | | 3ln(14)+6ln(3)= | | X^2+5x-1500=0 | | p+q=px+qy | | 63-62.5/2.1 | | In*(5x-6)+In*(x-6)=In*36 | | 6(x-2)-(x-3)=5-4(10-x) | | 1y=7x^3+4x | | x+0.6*x=130 | | 9x^2-6x+106=0 | | (D^3-5D+8D-4)y=E^2X | | (4x+10)+4x+x=46 | | 3k^4-k^2-24=0 | | 4x-11=5x+10 | | -3-2.9=-9x-0.5 | | (X+3)(8-x)=0 | | x-11=3x-21 | | 6x+5x-3x=32 | | x^2-4x+y^2+6y+z^2+8z+4=0 | | 72°/180°=x/π | | X+1.2(0.8-X)=0.18 | | 320=3x*x | | 7x-x^2-6=0 | | 320=x+x | | 2*-12-5=-19 | | 54.3x*1.5=8(0.3x-3) | | 72c+6=164 |